Universal method for the synthesis of arbitrary polarization states radiated by a nanoantenna. Issue 3 (25th February 2014) - Rodríguez‐Fortuño, Francisco J.; Puerto, Daniel; Griol, Amadeu; Bellieres, Laurent; Martí, Javier; Martínez, Alejandro
<x xml:space="preserve">Abstract</x> A simple way to synthetize the polarization of the radiation emitted by a single two‐input nanoantenna so that every point on the Poincaré sphere becomes attainable is shown. The nanoantenna is created on a CMOS compatible silicon chip using standard top‐down nanofabrication tools, but the method is universal and can be applied to other materials, wavelengths and technologies. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>